A comparative study of two techniques of laparoscopic orchiopexy for intra-abdominal testis - Azhar, Muhammad; Jalil, Shazia; Jaganathanb, Parameaswari Parthasarathy; Bajaber, Omar; Alabidi, Ghaida Abdullah; Shaikh, Mishraz; Hamidi, Saad Al; Alfifi, Khaled; Elkadi, Tarek Talaat Harb; Ali, Abdelbasit E.; Wahid, Fazal Nouman (International Surgery Journal, 2025)
Background: This study compares Fowler-Stephens and Shehata techniques for intra-abdominal testes, evaluating outcomes in testicular viability, positioning, and size to guide optimal surgical management. Methods: This retrospective study analyzed patients undergoing two-stage Shehata or Fowler-Stephens laparoscopic orchiopexy (FSLO) for intra-abdominal testis (August 2016-September 2019), collecting baseline characteristics and postoperative outcomes for comparison. Results: A total of 20 patients who underwent two-stage laparoscopic orchiopexy were included in this study. The patients were divided into two groups based on the technique used: the Shehata group (n=11) and the FSLO group (n=9), with each group including one case of bilateral intra-abdominal testes. In the FSLO group, testicular atrophy was observed in 30% (3/10) of the cases, whereas in the Shehata group, no testicular atrophy was observed (p=0.011). In the Shehata group, 75% (9/12) of the testes achieved a normal scrotal position, whereas in the FSLO group, 60% (6/10) achieved a normal scrotal position (p=0.001). 75% of the testes had a normal size in the Shehata group, whereas only 30% had a normal size in the FSLO group (p=0.001). In the FSLO group, the scrotal position was more successfully achieved in children over 4 years (p=0.006). Conclusions: The Shehata technique better preserves vascularity and achieves scrotal positioning in children under 4 years, while FSLO shows superior outcomes in older children, making age a key factor in technique selection for intra-abdominal testis.